Religiously Exclusive, Socially Inclusive? A Religious Response - Reitsma, Bernhard; van Nes-Visscher, Erika (Amsterdam University Press, 2023)
Is it possible to be religiously exclusive and socially inclusive? How do we deal with those outside of our own religious community who have completely different and sometimes conflicting views on what should be considered true and right behaviour? What if a religious tradition orders the expulsion or killing of those who leave the faith community and adopt another worldview? This book focuses on biblical texts concerning exclusivity and apostasy, studying different interpretations of such texts. It starts with the Jewish and Christian tradition of the Hebrew Bible, continues with texts from the New Testament, and explores diverse social studies to find ways of understanding the relationship between exclusion and inclusion today. Part of this exploration is the interaction with Jewish and Islamic voices. The collection ends with a systematic and missiological reflection on the issues Christian churches and other religious communities must address today.